Effect of physical therapy intervention on thickness and ratio of the sternocleidomastoid muscle and head rotation angle in infants with congenital muscular torticollis: A randomized clinical trial (CONSORT). Issue 33 (20th August 2021) - Song, Seonghyeok; Hwang, Wonjeong; Lee, Seungwon
Abstract: Background: Early diagnosis as well as treatment is important in management of congenital muscular torticollis (CMT). The purpose of this study was to find an effective physical therapy modality to improve the sternocleidomastoid (SCM) muscle thickness, the ratio of the SCM muscle thickness on the affected side to that on the non-affected side (A/N ratio), and head rotation in infant under 3 months of age diagnosed with CMT. Methods and analysis: A single-blind, randomized clinical trial was conducted. Participants were assigned in one of the 3 study groups through randomization. The treatment was performed 3 times a week for 30 minutes until the head tilt was ≤5 degrees. Group 1 was treated by handling for active or active-assist movement, group 2 was treated with passive stretching, and group 3 was treated with thermotherapy. For general characteristics, a χ 2 test and 1-way analysis of variance were used. Intragroup differences were analyzed using a paired t test, and intergroup differences were analyzed using an age-adjusted analysis of covariance. Results: After the intervention, there was no significant difference between groups in terms of SCM thickness on the affected side and A/N ratio ( P > .05). Degree of head rotation on the affected side showed significant differences between groups ( P < .05), with Group 2 showing significantly better results than group 1 and group 3 ( P < .05, both). Conclusion: Passive stretching treatment was more effective than other treatments of this study for improvement in degree of head rotation in CMT infants under 3 months of age. Trial registration: The trial is registered at the Institutional Review Board of Sahmyook University (IRB number, 2-7001793-AB-N-012019103HR) and the Clinical Research Information Service (CRiS; registry number, KCT0004862)